Perampanel efficacy and safety by gender: Subanalysis of phase III randomized clinical studies in subjects with partial seizures. (11th June 2015) - Vazquez, Blanca; Yang, Haichen; Williams, Betsy; Zhou, Sharon; Laurenza, Antonio
Summary The antiepileptic drug (AED) perampanel is approved in ≥40 countries as adjunctive therapy for drug‐resistant partial seizures in patients with epilepsy. This post hoc analysis of pooled data from three phase III, double‐blind, randomized studies of perampanel examines between‐gender differences in perampanel efficacy and safety. Of the 1, 478 subjects in the pooled analysis (719 male, 759 female), 1, 109 were included in the pharmacokinetic/pharmacodynamic analysis. Perampanel oral clearance was 17% lower in female than in male patients not receiving enzyme‐inducing AEDs. Pooled efficacy analysis revealed that seizure frequency was reduced with perampanel treatment regardless of gender; a greater numerical reduction in seizure frequency and increased responder rates occurred in female participants at perampanel doses of 4, 8, and 12 mg. Tolerability was similar between groups, although common adverse events such as dizziness and headache occurred more frequently in female subjects. Modest elevations in perampanel exposure in female patients may result in meaningful between‐gender differences in efficacy and safety; therefore, dosing should be individualized and clinical response monitored.